Entrepreneurial potential, realism and optimism as predictor variables of entrepreneurial intention: differences between Spain and Portugal - Sánchez García, José Carlos (2017)
In the psychological literature, intentions appear to be a good predictor of future planned behavior (Ajzen, 1991). This factor is directly associated with people's ability to create a business and self-employment as a strategy of progress and independence. The present study is an attempt to analyze whether there are differences between university students in Spain and Portugal regarding entrepreneurial intention and potential using the PROE instrument (Pessimism, Realism, Optimism and Entrepreneurship). The sample comprises 110 university students with a mean age of 21 years, 68.8% of whom were women and 29.5% were men. All factors evaluated have good internal consistency, and it was concluded that there are significant differences between Spanish and Portuguese students in their entrepreneurial potential, realism and optimism, with the establishment of social networks and economic motivation being the differential factors in the two populations.